Electrochemical oxidation of perfluorooctanesulfonate (PFOS) from simulated soil leachate and landfill leachate concentrate - Karatas, Okan; Khataee, Alireza; Kobya, Mehmet; Yoon, Yeojoon (Elsevier, 2023)
The near-widespread presence of poly- and perfluoroalkyl substances (PFASs) in humans has generated concerns regarding the potential negative impact of these chemicals on human health, as some PFASs are exceedingly persistent and bioaccumulative. Among the perfluorinated PFASs, which exhibit high polarity and strong carbon-fluorine bonds, perfluorooctanesulfonate (PFOS) is one of the frequently encountered species. In this study, the efficiency of electrooxidation (EO) and its application in groundwater simulation were first evaluated as a realistic approach to PFOS removal. After optimizing EO parameters including the solution pH, current density, and the effects of inlet concentration and the anode material, 83 % total organic carbon (TOC) removal was obtained. In groundwater experiments, in which the infiltration of PFOS from soil layers into groundwater was simulated, 79 % TOC removal efficiency was achieved in the more complex groundwater; moreover, an F- ion concentration of 8.78 mg/L was obtained from the decomposition of PFOS. To increase the realism of the simulation, the leachate process was repeated four times, and the EO process was applied to each sequential leachate. In addition, the process efficiency was studied in real landfill leachate wastewater to which PFOS had been added. Despite the challenging wastewater composition, 84 % TOC removal efficiency was achieved. Together, these results indicate that BDD-anodic oxidation may be a practical method to treat PFOScontaminated groundwater and wastewater.
Keywords: Electrochemical treatment; PFASs; Groundwater treatment; Landfill leachate treatment